Costs and benefits of insecticide and foliar nutrient applications to huanglongbing-infected citrus trees - Tansey, James A.; Vanaclocha, Pilar; Monzó, César; Jones, Moneen M.; Stansly, Philip A. (2018)
Background: The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama (Hemiptera: Psyllidae), vectors Candidatus Liberibacter asiaticus, which causes huanglongbing (HLB). In Florida, HLB incidence is approaching 100% statewide. Yields have decreased and production costs have increased since 2005. Despite this, some growers are maintaining a level of production and attribute this in part to aggressive psyllid control and foliar nutrition sprays. However, the value of these practices is debated. A replicated field study was initiated in 2008 in a commercial block of Valencia' sweet orange trees to evaluate individual and combined effects of foliar nutrition and ACP control. Results from 2012-2016 are presented. Results: Insecticides consistently reduced ACP populations. However, neither insecticide nor nutrition applications significantly influenced HLB incidence or PCR copy number in mature trees. In reset trees, infection continued to build and reached 100% in all treatments. Greatest yields (kg fruit ha(-1)) and production (kg solids ha(-1)) were obtained from trees receiving both insecticides and foliar nutrition. Conclusions: treatments resulted in production and financial gains relative to controls. However, material and application costs associated with the nutrition component offset these gains, resulting in lesser benefits than insecticides applied alone.